Heat Stress and Feed Restriction Distinctly Affect Performance, Carcass and Meat Yield, Intestinal Integrity, and Inflammatory (Chemo)Cytokines in Broiler Chickens - Emami, Nima K.; Greene, Elizabeth S.; Kogut, Michael H.; Dridi, Sami (Frontiers in Physiology, 2021)
This study was conducted to distinguish between the effects of heat stress and feed intake on broiler chicken’s performance, carcass and body parts yield, immune response and gut integrity. Day-old male Cobb 500 broiler chicks (n=720) were randomly allocated to three treatments with 8 replicates of 28 birds/pen including: 1) control (CTL): birds raised under normal temperature (23oC) from d 29-42 and had free access to the diet; 2) Cyclic heat stress (CHS): birds exposed to high temperatures (8 h/d at 35oC; from 9:30 am-5:30 pm) from d 29-42 and had free access to the diet; 3) pair-fed (PF): birds raised under the same condition as CTL group, but fed the same amount of feed as HS group from d 29-42. All birds were fed a corn-soybean meal basal diet. Feed and water consumption were measured daily and body weight measured weekly. On d 42, 15 birds/pen were processed and carcass parts were weighed. Core body temperature from 8 birds/treatment were recorded from d 29-42 using thermologgers. Core body temperature was increased ~1oC during the CHS period in the CHS group, as compared to the CTL and PF birds. Core body temperature was increased ~1oC during the CHS period in the CHS group, as compared to the CTL and PF birds. that gut barrier integrity was significantly altered in Post-CHS and AHS compared to CTL. Blood cytokine, chemokine, inflammasomes, heat shock proteins (HSP), and antioxidants analysis showed significantly higher mRNA abundances of TNF-α, CCL-20, HSP-27, and HSP-70 in Post-CHS and AHS groups compared to CTL. However, AHS was the only group with significantly higher mRNA abundances of NLRC-3 and NLRC-5, and lower SOD-1 and SOD-2 abundance compared with CTL. PF had significantly higher liver weight (% BW) compared to all other groups; while abdominal fat was significantly higher in Pre-CHS compared to CTL, PF, and AHS. Together, these data indicate distinct effects of FI and HS on broiler chicken’s performance, body parts yield, immune response, gut integrity and organ weight.